CB pattern in the harbour porpoise: Bioaccumulation, metabolism and evidence for cytochrome P450 IIB activity - Bruhn, Regina; Kannan, Narayanan; Petrick, Gert; Schulz-Bull, Detlef E.; Duinker, Jan C. (Chemosphere, 1995)
Metabolism of chlorobiphenyls (CBs) was studied in harbour porpoise by comparing patterns of CB-X/CB-153 ratios in blood, brain, liver and blubber with the patterns in herring, the main food source. The CBs were classified in five groups, based on the presence/absence of vicinal H-atoms (vic. Hs) in meta,para (m,p) and/or ortho,meta (o,m) positions and the number of ortho-Cl-atoms (ortho-Cls). Plots of CB-X/CB-153 ratios in porpoise tissue vs the ratios in herring appeared to be linear for each CB group in all tissues. Slopes of these plots (metabolic slopes) were used as quantitative indicators of metabolic activity. In this way, activity of PB-type isozymes of the P450 monooxygenase system was apparent: in contrast to existing literature data, harbour porpoise appears to be able to metabolize congeners with m,p vic. Hs, even in the presence of more than 2 ortho-Cls. The presence of 3-MC-type (MC-type) isozymes was also detected. The metabolic slopes were also used as basis for risk assessment. Due to their metabolism the most toxic non-ortho CBs were not present in the tissues at detectable levels. We suggest a risk assessment approach which takes this into account. It is considered to be an alternative and more reliable basis for risk assessment than the use of toxic equivalent factors. The results support the model of equilibrium distribution of CBs in harbour porpoise and the role of blood as central transport medium. The model has been developed for persistent compounds; it appears to hold for metabolizable CB congeners as well.